Quality Awareness of Indonesian Higher Education During the Covid-19 Pandemic: A Google Trend Analysis - Nur Adzidzah (Journal of Quality Assurance in Islamic Education (JQAIE), 2021)
This study aims to determine the trend of society on the quality of higher education and the factors that influence it during COVID-19. Data was collected through the google search engine in the period March 2020 to November 2021. Bibliometric analysis techniques based on Google Trend big data were used. The results of the study found that 1) the community trend regarding the quality of higher education was quite good with a range of information retrieval above 10% and a sharp increase during the July period; 2) two main factors influence the trend of awareness of the quality of higher education, namely the acceptance of new students, and monitoring of accreditation ratings by BAN-PT. Therefore, higher education institutions must continue to improve binding quality services through accreditation instruments, especially on websites or online media owned by universities.